Pacific modulation of the North Atlantic storm track response to sudden stratospheric warming events - Afargan-Gerstman, Hilla; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X (American Geophysical Union, 2020)
ISSN:0094-8276 ISSN:1944-8007